Using data to track racehorse physiology during training and racing - Schrurs, Charlotte B. (2024)
This thesis investigates multiple aspects of racehorse training, physiology, and performance. The overarching objective of the work is to explore the various factors that may influence the development of racehorses in-training, where a dearth of information exists, historically due to technological limitations. Here, by using a validated fitness tracker, the 'Equimetre™' then multiple aspects of racehorse physiology (heart rate, heart rate recovery), speed (GPS tracked), stride and on-course performance (results-based) could be analysed in large cohorts of racehorses. All studies were retrospective and observational.